Colorless transparent recombinant humanized collagen-thiolated hyaluronic acid composite hydrogel and preparation method and application thereof
Patent Information
- Application Number
- CN202610187821.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-02-10
AI Technical Summary
[0007]为了解决上述现有技术中重组人源化胶原蛋白溶于水形成的溶液动力粘度低、流动性大易于从病灶流失,且耐热性差、使用量大的技术问题,以及同时要解决现有产品不透明导致潜在异物杂质炎症反应的技术问题、胶原蛋白被化学交联和/或物理交联而被交联网络固定从而无法发挥更有效的应用效果的技术问题,本发明提供无色透明的重组人源化胶原蛋白-巯基化透明质酸复合水凝胶及其制备方法和应用
[0036](1)模拟了人体细胞外基质的天然构成,同时具有重组人源化胶原蛋白和透明质酸两种细胞外基质主要成分,综合了重组人源化胶原蛋白和透明质酸的各自生物学功能;
Smart Images

Figure CN121695258B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymeric gel biomaterials technology, specifically to a colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel, its preparation method, and its application. Background Technology
[0002] Collagen is a major component of the extracellular matrix, widely distributed in human connective tissue. It possesses unique tissue structure and biological functions, playing a crucial role in maintaining the extracellular environment, preserving the normal physiological functions of tissues and organs, and repairing bodily damage. It has been widely applied in the pharmaceutical, food, and daily chemical industries. However, the source of natural human collagen is limited. Currently, industrially used natural collagen is mainly extracted from animal skin or bones using acid, alkali, or enzymatic methods. Its primary source is animal connective tissue, which carries risks such as animal-derived diseases and immune rejection.
[0003] The basic structural unit of natural collagen is a right-handed triple helix structure formed by three left-handed polypeptide chains. The single chain usually has a Gly-XY repeating sequence, where Gly is glycine, and X and Y are mostly proline (Pro) and hydroxyproline (Hyp). Glycine is located in the core region of the helix, and its small volume helps the three chains to be tightly wrapped together. Hydroxyproline enhances the stability of the triple helix structure through hydrogen bonds. Natural collagen molecules can be further assembled to form collagen fibrils and build collagen fibers, which form a mechanical framework that supports tissue structure (Ramshaw et al., J Struct Biol., 1998,122 (1-2):86-91; Berisio et al., J Am Chem Soc., 2004, 126(37):11402-3; Brodsky et al., Biopolymers 2008, 89(5):345-53).
[0004] Recombinant humanized collagen is a recombinant protein that is modified or resynthesized from a segment of the human collagen gene sequence and then expressed through a host protein expression system. This solves the shortcomings of animal-derived collagen, such as poor water solubility, viral risks, and immune rejection. Recombinant humanized collagen is biodegradable and has good biocompatibility, thus it has broad application prospects in the biomedical field (Fertala, Bioengineering (Basel), 2020, 7(4):155; Cao et al., Front Bioeng Biotechnol., 2024, 12:1358246). Studies have found that recombinant collagen can regulate the disease microenvironment at the lesion site, promote the repair and regeneration of damaged tissues, and show good potential in the repair and treatment of various traumatic diseases. However, recombinant humanized collagen is easily soluble in water to form a thin, low-viscosity solution, resulting in severe loss when applied locally to damaged tissues, short duration of action at the lesion site, and urgent need to improve the therapeutic effect (CN115804750A). In addition, animal-derived and recombinant humanized collagen generally have poor heat resistance. The conventional moist heat sterilization temperature conditions (usually 121℃) of biopharmaceutical products will lead to their thermal degradation, thereby losing their mechanical properties and / or biological activity (Berisio et al., J Am Chem Soc., 2004, 126(37):11402-3; Perikov et al., Biochemistry 2005, 44(5):1414-22).
[0005] The existing technology CN119390816A uses cross-linking agents such as glutaraldehyde and 1,4-butanediol glycidyl ether (BDDE) to chemically cross-link recombinant human collagen, thereby forming a gel and finally preparing a porous scaffold. However, the preparation process is complex, and the residual cross-linking agent poses a risk of toxic side effects. The scaffold material is difficult to adhere well to the lesion site, especially when applied to wounds with complex shapes, it is even more difficult to fully cover and fit the complex wound shape. It has great limitations in the repair and treatment of traumatic diseases. To address the aforementioned issues and improve the repair capabilities of wound dressings, CN117180494A discloses an injectable polysaccharide hydrogel that can reduce the formation of fibrotic scars. This hydrogel has a double cross-linked network structure composed of photocrosslinked modified recombinant type III human collagen and cross-linked thiolized hyaluronic acid. However, it has limitations such as the need for photoinitiators, the potential for excessive photocrosslinking group modification (65%~100%) to impair the bioactivity of recombinant human collagen, the high cost (100~225 mg / ml) due to the large amount of recombinant human collagen required, and the complex application process.
[0006] To address the shortcomings of cartilage repair gel materials, such as easy shrinkage and poor cell adhesion, existing technology CN108084461A discloses a controllable self-crosslinking thiol-hyaluronic acid-collagen composite hydrogel. This hydrogel is composed of crosslinked thiolized hyaluronic acid hydrogel and natural type I collagen extracted from bovine tendon. The thiolized hyaluronic acid exhibits a high degree of thiol modification (30%–70%), and the product is milky white. Due to the physical self-assembly and crosslinking between the natural type I collagen and the thiolized crosslinking network, the collagen is thus fixed by the crosslinking network, resulting in good cell adhesion. However, the good cell adhesion effect of this natural type I collagen fixed by the crosslinking network is not conducive to specific application scenarios (such as postoperative adhesion repair treatment), and the milky white color of the product hinders the quality control of visible foreign matter and other impurities. Visible foreign matter and other impurities can lead to toxic side effects such as inflammatory reactions, requiring strict control. The opaque appearance severely interferes with the inspection and quality control of visible foreign matter. Summary of the Invention
[0007] To address the technical problems of low dynamic viscosity, high fluidity, easy loss from lesions, poor heat resistance, and large usage of recombinant human collagen solutions in water, as well as the technical problems of opacity leading to potential foreign body impurities and inflammatory reactions, and the technical problems of collagen being fixed by cross-linked networks due to chemical and / or physical cross-linking, thus failing to exert a more effective application effect, this invention provides a colorless and transparent recombinant human collagen-thiolized hyaluronic acid composite hydrogel, its preparation method, and its application. The recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel product of this invention is colorless and transparent with a semi-interpenetrating polymer network structure. That is, the product contains only a cross-linked network formed by thiolized hyaluronic acid, and the recombinant humanized collagen does not participate in any cross-linking. It is uniformly distributed in the cross-linked network in a free molecular state with its complete molecular structure and is embedded in the cross-linked network, which helps to maintain its complete biological activity. It can be gradually and slowly diffused and released under the action of body fluids to achieve a continuous therapeutic effect, and the dosage is low. It has good dynamic viscosity and wound adhesion and conformability, and presents as a viscous gel that can adhere to and cover wound tissue in all directions and prolong the time of action at the lesion site. At the same time, it has good heat resistance.
[0008] A key objective of this invention is to improve the wound repair effect of recombinant humanized collagen. To achieve this objective, it is necessary to preserve the bioactive functions of recombinant humanized collagen as much as possible, which requires maintaining its original molecular structure. Therefore, to achieve the above objective, this invention is implemented through the following technical solution:
[0009] The first aspect of this invention provides a colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel. The composite hydrogel has a semi-interpenetrating polymer network structure. The thiolized hyaluronic acid forms a cross-linked network through a self-cross-linking reaction between thiol groups. The recombinant humanized collagen does not undergo cross-linking and is uniformly distributed and embedded in the cross-linked network. The degree of modification of the thiolized hyaluronic acid is 0.5% to 2%. The content of the thiolized hyaluronic acid in the composite hydrogel is 3 mg / mL to 15 mg / mL.
[0010] In the composite hydrogel provided by this invention, no cross-linking agent is needed. The thiol groups of the thiolized hyaluronic acid spontaneously form a disulfide bond cross-linking network, avoiding the toxic side effects of residual cross-linking agents. Furthermore, the recombinant humanized collagen does not participate in cross-linking and does not undergo a chemical cross-linking reaction. It remains uniformly distributed in its original molecular form within the disulfide bond cross-linked hyaluronic acid network, forming a semi-interpenetrating polymer network structure. When the composite hydrogel provided by this invention is applied to the lesion site, the recombinant humanized collagen molecules can gradually diffuse and release from the semi-interpenetrating polymer network under the influence of body fluids, achieving a sustained-release effect for continuous therapeutic effect and improving treatment efficacy. The semi-interpenetrating polymer network structure composite hydrogel of this invention differs from the physical mixing of recombinant humanized collagen molecules and cross-linked hyaluronic acid gel. The composite hydrogel of this invention is a single-phase homogeneous gel uniformly dispersed at the molecular level, while physical mixing results in a non-homogeneous two-phase gel where cross-linked hyaluronic acid gel particles are dispersed in a recombinant humanized collagen solution. Physical mixing cannot achieve the slow release of recombinant collagen.
[0011] To achieve the objectives of this invention, the composite hydrogel provided by this invention needs to possess sufficient dynamic viscosity. If the dynamic viscosity is too low, the hydrogel will have high fluidity, easily run off the lesion site, resulting in short treatment time and poor efficacy. Furthermore, the composite hydrogel provided by this invention should also achieve good adhesion and conformation to the lesion application site, especially when applied to lesions with complex shapes (such as body cavities), achieving comprehensive coverage for a complete therapeutic effect. Compared to hydrogels that require in-situ cross-linking at the lesion site (CN117180494A, which need to be prepared and used immediately), the pre-formed composite hydrogel provided by this invention has many advantages. The composite hydrogel of this invention can be pre-filled into containers such as syringes, requiring no additional operations during clinical application; it can be directly injected into the lesion site, simplifying the treatment process and facilitating timely and rapid treatment for patients. However, improving the adhesion and conformation performance of the pre-formed hydrogel at the lesion site is a challenge, requiring a balanced and optimized design of various preparation parameters. This invention has found that the degree of modification and / or content of thiolated hyaluronic acid does not always have a simple positive correlation with wound adhesion. Excessively high modification levels (>2.03%) and / or contents (>15 mg / mL) not only fail to improve wound adhesion performance but may even impair it. Therefore, this invention employs a technical solution different from prior art CN117180494A and CN108084461A.
[0012] This invention optimizes key parameters such as the degree of modification and content of thiolated hyaluronic acid, and the content of recombinant humanized collagen. The composite hydrogel provided by this invention uses thiolated hyaluronic acid with a lower degree of modification (0.5%~2%) and a lower content (3 mg / mL~15 mg / mL).
[0013] Preferably, the degree of modification of the thiolized hyaluronic acid is 0.7% to 1.2%.
[0014] Preferably, the content of the thiolated hyaluronic acid in the composite hydrogel is 4 mg / mL to 10 mg / mL. More preferably, the content of the thiolated hyaluronic acid in the composite hydrogel is 5 mg / mL to 8 mg / mL.
[0015] Furthermore, the thiolated hyaluronic acid can be prepared by thiolation modification of the carboxyl group of the side chain of hyaluronic acid or its salt. The preparation method can be found in the methods disclosed by Shu et al. Biomacromolecules 2002, 3:1304-1311, CN104892962A, CN102399295A, etc.
[0016] Furthermore, the hyaluronic acid or its salt, which forms the basis for thiolation modification, has a weight-average molecular weight of 0.05 MDa to 3.0 MDa. Preferably, the hyaluronic acid or its salt has a weight-average molecular weight of 0.1 MDa to 1.0 MDa, and particularly preferably, the hyaluronic acid or its salt has a weight-average molecular weight of 0.15 MDa to 0.5 MDa.
[0017] Furthermore, the content of the recombinant humanized collagen in the composite hydrogel is 1 mg / mL to 20 mg / mL. Preferably, the content of the recombinant humanized collagen in the composite hydrogel is 3 mg / mL to 10 mg / mL.
[0018] Furthermore, the recombinant humanized collagen is selected from one or more of recombinant type I humanized collagen, recombinant type III humanized collagen, recombinant type V humanized collagen, and recombinant type XVII humanized collagen. Preferably, the recombinant humanized collagen is selected from recombinant type I humanized collagen and / or recombinant type III humanized collagen. More preferably, the recombinant humanized collagen is selected from recombinant type III humanized collagen.
[0019] Furthermore, the recombinant humanized collagen has a molecular weight greater than 10 kDa, preferably greater than 20 kDa.
[0020] Furthermore, in the existing technology CN108084461A, natural collagen solutions gel under physiologically neutral conditions due to physical self-assembly and cross-linking, exhibiting a viscoelastic solid (gel). Recombinant humanized collagen differs from natural collagen; it is readily soluble in water, forming a thin liquid, typically with a dynamic viscosity of less than 300 mPa·s, far inferior to natural collagen gel. Consequently, recombinant humanized collagen suffers significant loss when applied topically to damaged tissues, has a short duration of action at the lesion site, and results in unsatisfactory therapeutic effects. Therefore, the composite hydrogel provided by this invention has a very high dynamic viscosity, exhibiting a viscous gel state. The dynamic viscosity of the composite hydrogel provided by this invention is more than 100 times higher than that of the corresponding single recombinant humanized collagen solution. The fluidity of the composite hydrogel of this invention is significantly reduced, thus exhibiting better adhesion and conformation to lesions or wounds. This is highly beneficial for comprehensive adhesion and coverage of lesions or wound tissues, prolonging the action time at the lesion or wound site, and improving the therapeutic effect. Furthermore, it has a semi-interpenetrating polymer network structure, allowing for the slow release of recombinant humanized collagen. Although the cell adhesion rate is low, the sustained release of recombinant humanized collagen can improve the therapeutic effect. Therefore, the dynamic viscosity of the composite hydrogel of this invention is preferably greater than 5 × 10⁻⁶. 4 mPa·s; particularly preferably, the dynamic viscosity of the composite hydrogel is greater than 10 × 10 mPa·s. 4The above effects can be achieved at mPa·s.
[0021] Furthermore, the composite hydrogel of this invention has a colorless and transparent appearance, while existing technologies such as CN108084461A and CN112618800A are opaque or semi-transparent milky white gels. A colorless and transparent appearance is an important performance indicator for biopharmaceutical products, aiding in the quality control of visible foreign matter and other impurities. Visible foreign matter can cause toxic side effects such as inflammatory reactions and requires strict control; an opaque appearance would severely interfere with the inspection and quality control of visible foreign matter. In addition, the colorless and transparent nature also facilitates direct monitoring of the therapeutic effect after clinical use.
[0022] A second aspect of the present invention provides a method for preparing the above-mentioned colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel, comprising the following steps:
[0023] S1. Dissolve recombinant humanized collagen in an aqueous solvent to form a first solution, adjust or not adjust the pH of the first solution to a physiologically acceptable neutral range, and perform or not perform aseptic filtration;
[0024] S2. Dissolve thiolized hyaluronic acid in an aqueous solvent to form a second solution, adjust or not adjust the pH of the second solution to a physiologically acceptable neutral range, and perform or not perform aseptic filtration;
[0025] S3. Mix the first solution and the second solution evenly according to the formula, and perform sterile filtration or not. After mixing, the thiol groups of the thiolized hyaluronic acid in the second solution form a self-crosslinking network of disulfide bonds under the action of oxygen. After the crosslinking is stabilized, a colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel is obtained.
[0026] Furthermore, the preparation method also includes a moist heat sterilization process, wherein the moist heat sterilization process is performed immediately after the first solution and the second solution are mixed evenly, or after the cross-linking is stabilized to obtain a colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel;
[0027] The temperature of the moist heat sterilization process is in the range of 120℃ to 123℃, and the sterilization time is at least 15 minutes.
[0028] The composite hydrogel provided by this invention can withstand the standard moist heat sterilization level (typically 121°C) required for biopharmaceutical products, exhibiting excellent heat resistance and effectively meeting the sterility assurance level (SAL<10) for clinical applications. -6However, non-standard sterilization methods such as ultraviolet irradiation pose safety risks, such as incomplete sterilization (CN117180494A). The above preparation method has the advantages of not requiring cross-linking agents or other additives, producing water as the product, having a simple process, being easy to mass-produce, and having low manufacturing costs. In addition, the aseptic quality requirements of the composite hydrogel provided by this invention can also be achieved through a filtration sterilization process. The first solution, the second solution, or their mixture in S3 can be filtered using standard aseptic filtration (usually a 0.22µm pore size filter) to remove microorganisms, but the preparation process is relatively complex and the production cost is relatively high.
[0029] Furthermore, the aqueous solvents mentioned in S1 and S2 are both selected from physiological saline and / or phosphate buffer; the physiologically acceptable neutral range is pH = 6.8~7.6; when the pH value is not adjusted in S1 and / or S2, the pH value is adjusted to a physiologically acceptable neutral range after the first solution and the second solution are mixed evenly in S3.
[0030] The composite hydrogel provided by this invention mimics the natural composition of the human extracellular matrix, possessing both collagen and hyaluronic acid, two major components of the extracellular matrix. It integrates the respective biological functions of collagen and hyaluronic acid, and when applied to lesion sites, it can better regulate the disease microenvironment and improve the repair and treatment effect. Hyaluronic acid is a non-sulfonated glycosaminoglycan composed of repeating disaccharide units (α-1,4-D-glucuronic acid and β-1,3-N-acetyl-D-glucosamine). It exists as a major component of the extracellular matrix in all connective tissues and also possesses good biocompatibility, unique physicochemical properties, and a biological function that promotes wound healing. The composite hydrogel provided by this invention has the above-mentioned unique composition, structure, properties, and biological functions. Therefore, the third aspect of this invention provides the application of the above-mentioned colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel in the biomedical field.
[0031] Furthermore, the composite hydrogel of the present invention has positive application prospects and significant advantages in various medical fields such as the repair and treatment of traumatic diseases. Specific applications include its use in the preparation of postoperative adhesion repair treatment agents, its use in the preparation of skin wound repair treatment agents, and its use in the preparation of postmenopausal urogenital syndrome (GSM) treatment agents.
[0032] The composite hydrogel provided by this invention has a semi-interpenetrating polymer network structure. Specifically, a disulfide bond cross-linking network spontaneously forms between the thiol groups of thiolized hyaluronic acid. Recombinant humanized collagen does not participate in any physical or chemical cross-linking and is uniformly distributed in the disulfide bond cross-linked hyaluronic acid network in its original and intact molecular form, possessing complete biological activity. Even at extremely low concentrations (e.g., 1-5 mg / mL), it exhibits significant therapeutic effects, effectively saving costs. For chemically cross-linked recombinant humanized collagen, a therapeutic effect is only possible when the content of recombinant humanized collagen is greater than 5% (i.e., 50 mg / mL) (CN115919751A). In a double-crosslinked injectable polysaccharide hydrogel composed of photocrosslinked modified recombinant type III humanized collagen and cross-linked thiolized hyaluronic acid, the content of recombinant type III humanized collagen needs to be as high as 100 mg / mL to 225 mg / mL (CN117180494A).
[0033] Furthermore, although recombinant humanized collagen possesses cell adhesion sites, this cell adhesion function is useless or even harmful in the repair and treatment of many traumatic diseases (such as postoperative adhesions). Unlike existing technologies such as CN108084461A, CN108084461A, and CN117180494A, in the composite hydrogel provided by this invention, the recombinant humanized collagen does not participate in cross-linking and is not fixed in the cross-linked network. Therefore, it cannot serve as an anchor point for cell adhesion fixation. Consequently, the composite hydrogel of this invention, due to its specific semi-interpenetrating polymer network structure, does not possess cell adhesion function. Therefore, the composite hydrogel of this invention has better efficacy in the treatment of postoperative adhesion repair and other applications.
[0034] Furthermore, in the composite hydrogel provided by this invention, it was unexpectedly discovered that recombinant humanized collagen and thiolated hyaluronic acid have a synergistic enhancing effect, which can significantly promote the cross-linking and gelation process and effectively improve manufacturing efficiency. Animal-derived natural collagen and its partial hydrolysates (such as gelatin) do not possess this synergistic enhancing effect.
[0035] The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel of the present invention has the following beneficial technical effects:
[0036] (1) It simulates the natural composition of the human extracellular matrix and has two main extracellular matrix components, recombinant humanized collagen and hyaluronic acid, thus combining the biological functions of recombinant humanized collagen and hyaluronic acid.
[0037] (2) Recombinant humanized collagen is fixed without chemical or physical cross-linking. It is uniformly and freely distributed in the thiolized hyaluronic acid cross-linking network with a complete molecular structure, which helps to maintain complete biological activity. It can be gradually and slowly diffused and released under the action of body fluids to achieve continuous therapeutic effect. Moreover, the dosage is low, which can significantly save costs.
[0038] (3) It has a low cell adhesion rate and good dynamic viscosity and wound adhesion. It is a viscous gel that can cover the wound tissue in all directions and prolong the time of action at the lesion site. It has good application effects, especially in the treatment of postoperative adhesion repair, skin wound repair, and postmenopausal urogenital syndrome.
[0039] (4) It has good heat resistance and can withstand the moist heat sterilization temperature conditions required for biopharmaceutical products, effectively meeting the sterilization requirements for clinical applications;
[0040] (5) It has a colorless and transparent appearance, which helps in the quality inspection and control of visible foreign matter and other impurities in biological products;
[0041] (6) No cross-linking agents and auxiliaries are used, which avoids the risk of toxic side effects of residual cross-linking agents and other reagents. The preparation process is simple, easy to mass-produce, uses less recombinant humanized collagen, has a short manufacturing time and low manufacturing cost.
[0042] (7) Recombinant humanized collagen and thiolized hyaluronic acid have a synergistic enhancing effect, which can significantly promote the cross-linking and gelation process and effectively improve the production efficiency. Attached Figure Description
[0043] Figure 1 This is a comparison graph of the dynamic viscosity of recombinant humanized collagen, gelatin and animal-derived collagen in Example 1;
[0044] Figure 2 This is a comparison chart of the dynamic viscosity of the composite hydrogels rhCol I-HASH, GeA-HASH, GeB-HASH, CCol I-HASH, and PCol I-HASH in Example 5, as well as the HASH simple cross-linked gel; in the figure, cross-linked HASH represents the HASH simple cross-linked gel.
[0045] Figure 3 The dynamic viscosity of the rhCol Ⅲ-HASH composite hydrogels prepared with different degrees of thiol modification in Example 6;
[0046] Figure 4The tissue adhesion properties of the rhCol Ⅲ-HASH composite hydrogel in Example 7 are shown in Figure (a), which shows the peel strength under different HASH thiolization modification degrees, and Figure (b) shows the adhesion rate under different HASH thiolization modification degrees.
[0047] Figure 5 The graph shows the effect of different HASH contents on dynamic viscosity in the rhCol Ⅲ-HASH composite hydrogel in Example 8.
[0048] Figure 6 The tissue adhesion properties of the rhCol Ⅲ-HASH composite hydrogel in Example 9 are shown in Figure 9; (a) shows the peel strength at different HASH contents, and (b) shows the adhesion rate at different HASH contents.
[0049] Figure 7 The sustained-release properties of the rhCol Ⅲ-HASH composite hydrogel and the physically mixed hydrogel in Example 10 are shown in Figure 10. Here, a represents the physically mixed hydrogel prepared with a HASH content of 5 mg / mL, b represents the physically mixed hydrogel prepared with a HASH content of 10 mg / mL, c represents the rhCol Ⅲ-HASH composite hydrogel prepared with a HASH content of 5 mg / mL, and d represents the rhCol Ⅲ-HASH composite hydrogel prepared with a HASH content of 10 mg / mL.
[0050] Figure 8 The cell adhesion properties of rhCol I-HASH composite hydrogel and rhCol III-HASH composite hydrogel in Example 11;
[0051] Figure 9 The effects of using rhCol III solution, cross-linked HASH hydrogel, and rhCol III-HASH composite hydrogel in the treatment of intrauterine adhesions were evaluated; (a) total AFS score, (b) number of glands, and (c) endometrial thickness.
[0052] Figure 10 The study aimed to evaluate the efficacy (vaginal index) of rhCol III solution, cross-linked HASH hydrogel, and rhCol III-HASH composite hydrogel in the repair treatment of menopausal urogenital syndrome (GSM). Detailed Implementation
[0053] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0054] Unless otherwise specifically stated, the numerical values set forth in these embodiments do not limit the scope of the invention. Techniques and methods known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques and methods should be considered part of the specification. In all examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values. It should be noted that values expressed, for example, as "within the range of ab" or "between the range of ab," do not include the endpoint values a and b; values expressed as "for ab," "is ab," or "ab" include the endpoint values a and b.
[0055] Furthermore, it should be noted that the use of terms such as "first" and "second" to describe the solution is merely for the purpose of distinguishing the substances obtained in each step. Unless otherwise stated, the above terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention.
[0056] Experimental methods not specified in the following examples are generally performed according to national standards; if there is no corresponding national standard, they are performed according to general standard requirements or general methods.
[0057] The academic definitions of some of the terms used in this invention are as follows:
[0058] Hydrogels are substances containing a large amount of water and having a three-dimensional cross-linked network structure. They exist between liquid and solid states and have no fluidity. Gelation refers to the process of changing from a fluid liquid state to a gel state that loses its fluidity.
[0059] Thiolated hyaluronic acid refers to a derivative of hyaluronic acid in which thiol groups are chemically introduced into the side chain. The degree of thiolization modification refers to the percentage of thiol groups introduced out of the total number of modifiable side chain groups in the hyaluronic acid, often also called the grafting rate. For example, when the carboxyl groups on the side chain of hyaluronic acid are thiolized, the degree of thiolization modification is the percentage of thiol groups introduced out of the total number of carboxyl groups on the hyaluronic acid side chain. The above description applies to the preparation of thiolized hyaluronic acid using hyaluronic acid or sodium hyaluronate.
[0060] Semi-interpenetrating polymer network (Semi-IPN) is a special type of interpenetrating polymer network (IPN). Its structural characteristic is that only one of the two polymer components forms a cross-linked network, while the other maintains a linear structure and does not undergo chemical cross-linking. This structure achieves interpenetration at the molecular level through physical entanglement. Since there are no covalent bonds between the components, the non-cross-linked components can be separated by solvent extraction without breaking the chemical bonds.
[0061] Dynamic viscosity refers to the force required to generate a unit flow velocity in a liquid layer per unit area over a unit distance. Its unit is centipoise (mPa·s) or poise (Pa·s). Dynamic viscosity is an indicator of viscosity; the lower the dynamic viscosity, the greater the fluidity, and vice versa.
[0062] Thiolized hyaluronic acid is abbreviated as HASH, recombinant type I humanized collagen is abbreviated as rhColⅠ, recombinant type III humanized collagen is abbreviated as rhCol Ⅲ, recombinant type V humanized collagen is abbreviated as rhCol V, recombinant type XVII humanized collagen is abbreviated as rhCol XVII, type A gelatin is abbreviated as GeA, type B gelatin is abbreviated as GeB, porcine type I collagen is abbreviated as PColⅠ, and bovine type I collagen is abbreviated as CColⅠ.
[0063] In the following examples, cross-linked HASH hydrogel, HASH simple cross-linked hydrogel, cross-linked HASH gel, simple HASH hydrogel, and cross-linked HASH all refer to cross-linked hydrogels that only have HASH.
[0064] Example 1
[0065] This case study compares the dynamic viscosity properties of recombinant human collagen, gelatin, and animal-derived collagen.
[0066] (1) Weigh appropriate amounts of recombinant humanized collagen rhCol I (molecular weight approximately 35 KDa), rhCol III (molecular weight approximately 55 KDa), rhCol V (molecular weight approximately 27 KDa), and rhCol XVII (molecular weight approximately 17.9 KDa) (recombinant humanized collagen was purchased from Juyuan Biotechnology), stir and dissolve in physiological saline, adjust the pH of the solution to 7.4, and obtain clear and transparent solutions of each type of recombinant humanized collagen with contents of 1 mg / mL, 5 mg / mL and 10 mg / mL, respectively.
[0067] (2) Solutions of type A gelatin (pig skin extract, GeA, molecular weight approximately 150-180 kDa, purchased from Rousselot) and type B gelatin (bovine bone extract, GeB, molecular weight approximately 120-150 kDa, purchased from Rousselot) of the same concentration, as well as solutions of porcine type I collagen (pig tendon extract, PCol I, molecular weight approximately 330 kDa, purchased from Chuang'er Biotechnology) and bovine type I collagen (bovine Achilles tendon extract, CCl I, molecular weight approximately 300 kDa, purchased from Chuang'er Biotechnology) were prepared as controls. The preparation methods of GeA and GeB solutions were the same as those for recombinant humanized collagen. The preparation process of PCol I and CCl I solutions was as follows: PCol I and CCl I were dissolved in 0.25 mol / L acetic acid solution in an ice bath to obtain solutions with contents of 1 mg / mL, 5 mg / mL and 10 mg / mL, respectively, and the pH of the solution was adjusted to 7.4.
[0068] The dynamic viscosity (0.28 Hz) was measured at 25℃ using an Anton Paar MCR-102 rheometer (PP-25 rotor). The results are shown in [Figure number missing]. Figure 1 See Table 1.
[0069] Table 1. Dynamic viscosity of protein solutions of different concentrations
[0070]
[0071] Depend on Figure 1 As shown in Table 1, recombinant humanized collagen (rhCol I, rhCol III, rhCol V, rhCol XVII) is readily soluble in water, exhibiting typical thin fluid properties and very low dynamic viscosity, all less than 300 mPa·s. Gelatin (GeA and GeB) are partially hydrolyzed products of porcine / bovine bone collagen, readily soluble in water, and their solution properties and dynamic viscosity are similar to those of recombinant humanized collagen. However, porcine type I collagen (PCol I) and bovine type I collagen (CCol I), at solution concentrations of 5 mg / mL and 10 mg / mL respectively, both undergo gelation due to physical self-assembly cross-linking, exhibiting a translucent, milky-white viscoelastic solid (gel), with a dynamic viscosity much greater than that of recombinant humanized collagen and gelatin solutions.
[0072] Example 2
[0073] This case study focuses on the preparation of thiolated hyaluronic acid.
[0074] Thiodipropionylhydrazine-modified thiolated hyaluronic acid was prepared according to the method disclosed in Shu et al. Biomacromolecules 2002, 3:1304-1311.
[0075] 5 g of hyaluronic acid (117 kDa) was dissolved in 500 mL of distilled water, and 5 g of dithiodipropionylhydrazine was added and stirred until dissolved. The pH of the system was then adjusted to 4.75 with 0.1 mol / L hydrochloric acid solution. Different weights of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) were added according to the amounts shown in Table 2 below, and the mixture was stirred magnetically. A suitable amount of 0.1 mol / L hydrochloric acid solution was continuously added to the above solution to maintain the pH at 4.75. The reaction was terminated by adding 1 mol / L sodium hydroxide solution until the pH reached 7.0. Then, 20 g of dithiothreitol (DTT) and a suitable amount of 1 mol / L sodium hydroxide solution were added, stirred, and the pH of the solution was adjusted to 8.5. The reaction was carried out at room temperature with magnetic stirring for 24 hours. Afterward, 1 mol / L hydrochloric acid solution was added to the above solution until the pH was approximately 3.0. The above solution was loaded into a dialysis tube (with a molecular weight cutoff of 3500 Da) and dialyzed for 5 days with a large amount of 0.001 mol / L hydrochloric acid solution and 0.2 mol / L sodium chloride solution, changing the dialysate every 8 hours. Then, it was dialyzed for 3 days with a large amount of 0.001 mol / L hydrochloric acid solution, changing the dialysate every 8 hours. Finally, the solution in the dialysis tube was collected and used directly or freeze-dried to obtain a white flocculent solid.
[0076] The thiol content was detected and the degree of thiol modification was calculated using the improved Ellman method reported by Shu et al. (Biomacromolecules 2002, 3:1304-1311), or by proton NMR spectroscopy. 1 The degree of thiol modification was determined by ¹H-NMR (using D₂O as solvent) with the characteristic methyl absorption peak of the acetyl group of hyaluronic acid as an internal standard. The degree of thiol modification refers to the percentage of thiol groups introduced relative to the total number of carboxyl groups in the side chain of hyaluronic acid.
[0077] Table 2. Degree of thiolation modification of thiolated hyaluronic acid obtained with different EDCI feed amounts
[0078]
[0079] As shown in Table 2, the degree of thiolation modification of thiolated hyaluronic acid increases with the increase of EDCI feed amount.
[0080] Example 3
[0081] This case study focuses on the preparation of thiolated hyaluronic acid.
[0082] Thioyl hyaluronic acid modified with cystamine dihydrochloride was prepared according to the method reported in CN116178588A.
[0083] Sodium hyaluronate (658 kDa), cystamine dihydrochloride, and N-hydroxythiosuccinimide were dissolved in distilled water. The pH of the solution was adjusted to 4.75 by adding an appropriate amount of acid or base (0.1 mol / L hydrochloric acid solution or sodium hydroxide solution). Then, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDCI) was added, stirred to dissolve, and the pH of the reaction solution was kept stable at 4.75 for 30 minutes. An appropriate amount of 0.1 mol / L sodium hydroxide solution was added to raise the pH of the reaction solution to 6.0, and the reaction was stirred overnight. The pH of the reaction solution was adjusted to 8.5 by adding 1 mol / L sodium hydroxide solution, and the reaction was terminated. Then, dithiothreitol was added, stirred to dissolve, and the reaction was allowed to proceed for 4 hours. Finally, 1 mol / L hydrochloric acid solution was added to adjust the pH of the above reaction solution to 3.0. The above solution was loaded into a dialysis tube (molecular weight cutoff 3500 Da) and purified by dialysis with a mixed solution containing 0.001 mol / L hydrochloric acid and 0.2 mol / L sodium chloride. The purification process of the final product was monitored using gel permeation chromatography (GPC) until the impurity absorption peaks were no longer visible. Finally, the solution was dialyzed with 0.001 mol / L hydrochloric acid solution for desalting. The solution in the dialysis tube was collected and freeze-dried to obtain a white flocculent solid.
[0084] The thiol content was determined and the degree of thiol modification was calculated using the improved Ellman method reported by Shu et al. (Biomacromolecules 2002, 3:1304-1311). The degree of thiol modification refers to the percentage of thiol groups introduced relative to the total number of carboxyl groups in the hyaluronic acid side chain.
[0085] In this case, the molar ratio of sodium hyaluronate to cystamine dihydrochloride was 1:2, the molar ratio of EDCI to N-hydroxythiosuccinimide was 1:0.5, the molar ratio of cystamine dihydrochloride to dithiothreitol was 1:2, and the molar ratios of EDCI to sodium hyaluronate were 1:0.01, 1:0.02, 1:0.03, 1:0.05, 1:0.10, 1:0.15, and 1:0.20, respectively. The degree of thiolation modification of the thiolated hyaluronic acid prepared with the corresponding molar ratios was 0.52%, 0.71%, 1.18%, 2.03%, 3.07%, 5.01%, and 6.83%, respectively.
[0086] The above preparation method is also applicable to the preparation of thiolated hyaluronic acid with various molecular weights (e.g., 0.05 MDa to 3 MDa). Solutions of high molecular weight hyaluronic acid or sodium hyaluronate have higher viscosity, which reduces the corresponding reactivity. Therefore, under the same reaction conditions, the degree of modification of high molecular weight thiolated hyaluronic acid will be reduced, requiring an appropriate increase in the amount of EDCI. Adjusting the amount of EDCI allows for the preparation of thiolated hyaluronic acid with various degrees of modification.
[0087] Example 4
[0088] This case study demonstrates the preparation and appearance characterization of various hydrogels.
[0089] (1) The preparation of recombinant human collagen-thiolized hyaluronic acid composite hydrogel includes the following steps:
[0090] S1. Different recombinant humanized collagen proteins (rhCol I, rhCol III, rhCol V, rhCol XVII, the same as in part (1) of Example 1) were dissolved in physiological saline containing 5 mmol / L phosphate buffer to obtain recombinant humanized collagen protein solutions with a concentration of 10 mg / mL: rhCol I solution, rhCol III solution, rhCol V solution, and rhCol XVII solution. The pH of the solution was adjusted to 7.4.
[0091] S2. Dissolve the HASH (thiol modification degree 1.18%) prepared in Example 3 in physiological saline containing 5 mmol / L phosphate buffer to obtain a 10 mg / mL HASH solution, and adjust the pH of the solution to 7.4.
[0092] S3. Mix the recombinant humanized collagen solutions from S1 and the HASH solution from S2 in equal volume ratios and stir until homogeneous to obtain a recombinant humanized collagen-HASH mixed solution. Under the action of oxygen, the thiol groups of HASH form a self-crosslinking network of disulfide bonds. The recombinant humanized collagen-HASH mixed solution gradually gels and loses its fluidity (usually within 1-7 days at 40℃), thus obtaining the recombinant humanized collagen-HASH composite hydrogel, which are respectively named: rhCol I-HASH, rhColIII-HASH, rhCol V-HASH, and rhCol XVII-HASH, wherein the content of recombinant humanized collagen and HASH is 5 mg / mL.
[0093] The recombinant human collagen-thiolized hyaluronic acid composite hydrogel prepared in this section has a semi-interpenetrating polymer network structure. The thiolized hyaluronic acid forms a cross-linked network through the self-cross-linking reaction between thiol groups. The recombinant human collagen does not undergo cross-linking and is uniformly distributed and embedded in the cross-linked network.
[0094] (2) The recombinant humanized collagen solution in Part (1) S1 of this case was replaced with the GeA solution, GeB solution, CCl I solution and PCol I solution (each solution concentration was 10 mg / mL) prepared in Example 1. The corresponding gelatin-HASH composite hydrogel and type I collagen-HASH composite hydrogel were prepared using the same process as in Part (1) of this case. They were denoted as GeA-HASH, GeB-HASH, CCl I-HASH and PCol I-HASH, respectively, with each gelatin content of 5 mg / mL, each type I collagen content of 5 mg / mL and each HASH content of 5 mg / mL. These were used as control standards.
[0095] (3) The recombinant humanized collagen solution in Part (1) S1 of this case was replaced with physiological saline containing 5 mM phosphate buffer to prepare the corresponding simple HASH hydrogel (i.e., hydrogel with only HASH cross-linking network, referred to as HASH simple cross-linking gel) as a control, wherein the HASH content was 5 mg / mL.
[0096] The appearance characteristics of each group of gels are shown in Table 3.
[0097] Table 3 Appearance characteristics of gels in each group
[0098]
[0099] Table 3 shows that the simple cross-linked HASH gels and the composite hydrogels: rhCol I-HASH, rhCol III-HASH, rhCol V-HASH, rhCol XVII-HASH, GeA-HASH, and GeB-HASH are all colorless and transparent. The composite hydrogels PCol I-HASH and CCol I-HASH are both translucent milky white, indicating that type I collagen (Col I) undergoes physical self-assembly and cross-linking aggregation in the composite hydrogel.
[0100] Example 5
[0101] This case study demonstrates the preparation and dynamic viscosity characterization of various hydrogels.
[0102] (1) Preparation of recombinant human collagen-thiolized hyaluronic acid composite hydrogel, specifically the preparation of rhCol I-HASH composite hydrogel, including the following steps:
[0103] S1. Dissolve recombinant humanized collagen (rhCol I) in physiological saline containing 5mM phosphate buffer to obtain a 10mg / mL rhCol I solution, and adjust the pH of the solution to 7.4.
[0104] S2. Dissolve the HASH (modification degree 1.18%) prepared in Example 3 in physiological saline containing 5mM phosphate buffer to obtain a 10mg / mL HASH solution, and adjust the pH of the solution to 7.4.
[0105] S3. Mix the above rhCol I solution and HASH solution in equal volume ratio and stir evenly to obtain rhCol I-HASH mixed solution. Immediately perform moist heat sterilization treatment (121℃, sterilization time greater than 15 minutes, sterilization time in this case is 17.6 min). After sterilization, the thiol groups of HASH in the mixed solution form a self-crosslinking network of disulfide bonds under the action of oxygen. The mixed solution gradually gels and loses fluidity. After the crosslinking is stable, rhCol I-HASH composite hydrogel is obtained, wherein the contents of rhCol I and HASH are 5 mg / mL.
[0106] The recombinant human collagen-thiolized hyaluronic acid composite hydrogel prepared in this section has a semi-interpenetrating polymer network structure. The thiolized hyaluronic acid forms a cross-linked network through the self-cross-linking reaction between thiol groups. The recombinant human collagen does not undergo cross-linking and is uniformly distributed and embedded in the cross-linked network.
[0107] (2) The GeA solution, GeB solution, CCOl I solution and PCol I solution (each solution concentration is 10 mg / mL) prepared in Example 1 were used to replace the rhCol I solution in S1 of Part (1) of this case. The corresponding composite hydrogels were prepared using the same process as in Part (1) of this case and were denoted as GeA-HASH, GeB-HASH, CCOl I-HASH and PCol I-HASH, respectively. The gelatin content of each was 5 mg / mL, the type I collagen content was 5 mg / mL and the HASH content was 5 mg / mL.
[0108] (3) Replace the rhCol I solution in S1 of Part (1) of this case with physiological saline containing 5mM phosphate buffer and prepare the corresponding simple HASH hydrogel (i.e., hydrogel with only HASH cross-linking network, referred to as HASH simple cross-linking gel) as a control, wherein the HASH content is 5mg / mL.
[0109] The gels obtained after moist heat sterilization were allowed to stand at 40℃ for 2 days and 7 days, respectively. Then, the dynamic viscosity (0.28 Hz) was measured at 25℃ using a rheometer (Anton Paar MCR-102 rheometer, PP-25 rotor). The results are shown in [Figure number missing]. Figure 2 .Depend on Figure 2It is known that the combination of recombinant humanized collagen (rhCol I) and thiolated hyaluronic acid has a synergistic enhancing effect. rhCol I significantly promotes the gelation process of the composite hydrogel, effectively improving the production efficiency. The dynamic viscosity of the rhCol I-HASH composite hydrogel reaches a stable state after 2 days, which is superior to that of the simple HASH hydrogel. Figure 2 The cross-linked HASH (labeled as cross-linked HASH) is superior to GeA-HASH, GeB-HASH, CCOl I-HASH, and PCol I-HASH composite hydrogels. In the GeA-HASH, GeB-HASH, CCOl I-HASH, and PCol I-HASH composite hydrogels, animal-derived type I collagen (CCol I and PCol I) and gelatin (GeA and GeB) significantly hindered the gelation and disulfide bond cross-linking process of the HASH after moist heat sterilization, especially the latter.
[0110] Example 6
[0111] This case study examines the effect of different degrees of thiolation modification of HASH on the dynamic viscosity of recombinant humanized collagen (rhCol III)-thiolated hyaluronic acid (HASH) composite hydrogels.
[0112] The preparation of the rhCol III-HASH composite hydrogel in this case includes the following steps:
[0113] S1. Dissolve recombinant humanized collagen (rhCol Ⅲ) in physiological saline containing 5mM phosphate buffer to obtain a 10mg / mL rhCol Ⅲ solution, and adjust the pH of the solution to 7.4.
[0114] S2. Dissolve the seven HASH solutions with different degrees of thiol modification prepared in Example 3 in physiological saline containing 5 mM phosphate buffer to obtain 10 mg / mL HASH solutions with different degrees of thiol modification, and adjust the pH of the solution to 7.4.
[0115] S3. Mix the above rhCol Ⅲ solution and HASH solutions with different degrees of thiolization modification in equal volume ratios, stir evenly to obtain rhCol Ⅲ-HASH mixed solution, and immediately perform moist heat sterilization treatment (121℃, sterilization time greater than 15 minutes, in this case, the sterilization time is 17.2 min). After sterilization, the thiol groups of HASH in the mixed solution form a self-crosslinking network of disulfide bonds under the action of oxygen. The mixed solution gradually gels and loses fluidity. After the crosslinking is stable, rhCol Ⅲ-HASH composite hydrogel is obtained, wherein the contents of rhCol Ⅲ and HASH are 5 mg / mL, respectively.
[0116] The recombinant human collagen-thiolized hyaluronic acid composite hydrogel prepared in this case has a semi-interpenetrating polymer network structure. The thiolized hyaluronic acid forms a cross-linked network through the self-cross-linking reaction between thiol groups. The recombinant human collagen does not undergo cross-linking and is uniformly distributed and embedded in the cross-linked network.
[0117] In addition, the simple HASH hydrogel (i.e., hydrogel with only HASH cross-linking network, referred to as HASH simple cross-linking gel) prepared in part (3) of Example 5 was used as a control, wherein the HASH content was 5 mg / mL.
[0118] The gels in each group were allowed to stand at 40℃ for 7 days, and then the dynamic viscosity (0.28 Hz) was measured at 25℃ using a rheometer (Anton Paar MCR-102 rheometer, PP-25 rotor). The results are shown in the figure. Figure 3 .Depend on Figure 3 It can be seen that the dynamic viscosity of the rhCol Ⅲ-HASH composite hydrogel is better than that of the simple HASH hydrogel. Figure 3 The term "crosslinked HASH" is used to describe this property, and this advantage is particularly pronounced at both lower grafting rates (below 1%) and higher grafting rates (above 5%).
[0119] Example 7
[0120] This case study examines the tissue adhesion properties of rhCol Ⅲ-HASH composite hydrogels prepared using HASH with different degrees of thiol modification in Example 6.
[0121] The tissue adhesion properties of the seven rhCol III-HASH composite hydrogels prepared in Example 6 were characterized using the peel test method reported by Torres la Roche et al. (J Clin Med., 2022, 11, 931) (YYB-03 pharmaceutical packaging tear tester). This method simulates the adhesion properties of the gel to human tissue by measuring the peeling behavior of the gel on the surface of a hydrophilic paper strip. rhCol III-HASH composite hydrogel (40℃, 14 days of standing) was evenly coated on the surface of a square base (coated cardboard material) (65 mm × 80 mm × 2 mm). A hole was punched in one end of a cut A4 paper (7 cm × 29.7 cm) and a thin string was tied to it. The other end of the string was fixed to the clamp sensor of the testing instrument. Then, the A4 paper was placed on the surface of the composite hydrogel, and the peeling direction was close to 90°. The peeling speed was set to 300 mm / min. The test was started, and the peel strength results were recorded (unit: N / 15 mm). After the test, the weight of the composite hydrogel adhering to the test paper strip was weighed, and the adhesion rate (adhesion weight percentage) was calculated.
[0122] The peel strength results of each group of rhCol III-HASH composite hydrogels are shown in the figure. Figure 4 Figure (a) shows that the composite hydrogels prepared with lower thiol modification degree (0.52%~2.03%) HASH have similar and higher peel strength, while the composite hydrogels prepared with high modification degree (3.07%~6.83%) HASH have poor peel strength, even dropping to 0 (6.83% thiol modification degree).
[0123] The adhesion rates of each group of rhCol III-HASH composite hydrogels are shown in the figure. Figure 4 Figure (b) shows that the composite hydrogels prepared with HASH of lower thiol modification degree (0.52%~2.03%) have similar adhesion rates of over 90%, while the adhesion rate of the prepared composite hydrogels drops sharply to below 40% as the thiol modification degree in HASH increases (3.07%~6.83%).
[0124] The above results indicate that the continuous increase in the degree of HASH thiolation modification not only fails to improve the tissue adhesion properties of the composite hydrogel, but also impairs them.
[0125] Example 8
[0126] This case study examines the effect of different HASH contents on dynamic viscosity in rhCol Ⅲ-HASH composite hydrogels.
[0127] The preparation of the rhCol III-HASH composite hydrogel in this case includes the following steps:
[0128] S1. Recombinant humanized collagen (rhCol Ⅲ) was dissolved in physiological saline containing 5mM phosphate buffer to obtain a 9mg / mL rhCol Ⅲ solution. The pH of the solution was adjusted to 7.4.
[0129] S2. The HASH with a thiol modification degree of 1.18% prepared in Example 3 was dissolved in physiological saline containing 5 mM phosphate buffer to obtain HASH solutions with different HASH contents: 3 mg / mL, 4.5 mg / mL, 6 mg / mL, 7.5 mg / mL, 12 mg / mL, 15 mg / mL, 22.5 mg / mL and 30 mg / mL. The pH of the solution was adjusted to 7.4.
[0130] S3. The above rhCol Ⅲ solution and HASH solutions with different contents are mixed at a volume ratio of 1:2 and stirred evenly to obtain an rhCol Ⅲ-HASH mixed solution. Immediately perform moist heat sterilization treatment (121℃, sterilization time greater than 15 minutes, sterilization time in this case is 17.5 min). After sterilization, the thiol groups of HASH in the mixed solution form a self-crosslinking network of disulfide bonds under the action of oxygen. The mixed solution gradually gels and loses fluidity. After the crosslinking is stable, an rhCol Ⅲ-HASH composite hydrogel is obtained, wherein the rhCol Ⅲ content is 3 mg / mL, and the HASH content is 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 8 mg / mL, 10 mg / mL, 15 mg / mL and 20 mg / mL, respectively.
[0131] The gels in each group were allowed to stand at 40℃ for 7 days, and then the dynamic viscosity (0.28 Hz) was measured at 25℃ using a rheometer (Anton Paar MCR-102 rheometer, PP-25 rotor). The results are shown in the figure. Figure 5 .Depend on Figure 5 It is evident that the dynamic viscosity of the composite hydrogel is positively correlated with the HASH content; the dynamic viscosity increases significantly with increasing HASH content. At a HASH content of 2 mg / mL, the dynamic viscosity of the composite hydrogel is approximately 2 × 10⁻⁶. 4 mPa·s; when the HASH content is above 3 mg / mL, the dynamic viscosity of the composite hydrogel exceeds 5 × 10 mPa·s. 4 mPa·s; when the HASH content is above 8 mg / mL, the dynamic viscosity of the composite hydrogel exceeds 20 × 10 mPa·s. 4 mPa·s.
[0132] Example 9
[0133] This case study examines the tissue adhesion properties of rhCol Ⅲ-HASH composite hydrogels prepared with different HASH contents in Example 8.
[0134] The tissue adhesion properties of the eight rhCol III-HASH composite hydrogels prepared in Example 8 were characterized using the peel test method reported by Torres la Roche et al. (J Clin Med., 2022, 11, 931) (YYB-03 pharmaceutical packaging tear tester). This method simulates the adhesion properties of the gel to human tissue by measuring the peeling behavior of the gel on the surface of a hydrophilic paper strip. rhCol III-HASH composite hydrogel (40℃, 14 days of standing) was evenly coated on the surface of a square base (coated cardboard material) (65 mm × 80 mm × 2 mm). A hole was punched in one end of a cut A4 paper (7 cm × 29.7 cm) and a thin string was tied to it. The other end of the string was fixed to the clamp sensor of the testing instrument. Then, the A4 paper was placed on the surface of the composite hydrogel, and the peeling direction was close to 90°. The peeling speed was set to 300 mm / min. The test was started, and the peel strength results were recorded (unit: N / 15 mm). After the test, the weight of the composite hydrogel adhering to the test paper strip was weighed, and the adhesion rate (adhesion weight percentage) was calculated.
[0135] The peel strength results of each group of rhCol III-HASH composite hydrogels are shown in the figure. Figure 6 Figure (a) shows that the composite hydrogels prepared with HASH content of 2 mg / mL-15 mg / mL have high peel strength, but the peel strength of the composite hydrogels prepared by further increasing the HASH content to 20 mg / mL decreases.
[0136] The adhesion rates of each group of rhCol III-HASH composite hydrogels are shown in the figure. Figure 6 Figure (b) shows that the composite hydrogels prepared with HASH content of 3 mg / mL-15 mg / mL have a very high adhesion rate of over 90%, the composite hydrogels prepared with HASH content of 2 mg / mL have an adhesion rate of less than 80%, and the composite hydrogels prepared with HASH content of 20 mg / mL have an adhesion rate of less than 50%.
[0137] The above results indicate that a continuous increase in HASH content not only fails to improve the tissue adhesion properties of the composite hydrogel, but may even impair them.
[0138] Therefore, Examples 7 and 9 show that excessively high degrees of thiol modification (>2.03%) and / or HASH content (>15 mg / mL) not only do not improve wound adhesion performance, but may even impair it.
[0139] Example 10
[0140] This case study examines the sustained-release effect of the rhCol III-HASH composite hydrogel with a semi-interpenetrating polymer network structure prepared by the method of this invention and the physically mixed hydrogel on recombinant human collagen.
[0141] (1) Semi-interpenetrating polymer network structure rhCol III-HASH composite hydrogel: Two rhCol III-HASH composite hydrogels prepared in Example 8 were selected, with rhCol III content of 3 mg / mL and HASH content of 5 mg / mL and 10 mg / mL, respectively.
[0142] The recombinant human collagen-thiolized hyaluronic acid composite hydrogel prepared in this section has a semi-interpenetrating polymer network structure. The thiolized hyaluronic acid forms a cross-linked network through the self-cross-linking reaction between thiol groups. The recombinant human collagen does not undergo cross-linking and is uniformly distributed and embedded in the cross-linked network.
[0143] (2) Preparation of physically mixed hydrogels:
[0144] Recombinant humanized collagen (rhCol Ⅲ) was dissolved in physiological saline containing 5 mM phosphate buffer to obtain a 10 mg / mL rhCol Ⅲ solution, and the pH of the solution was adjusted to 7.4.
[0145] The HASH with a thiol modification degree of 1.18% prepared in Example 3 was dissolved in physiological saline containing 5 mM phosphate buffer to obtain HASH solutions with concentrations of 10 mg / mL and 20 mg / mL, respectively. The pH of the solution was adjusted to 7.4, and the solution was first allowed to stand at 40°C for 7 days to achieve complete cross-linking and form a cross-linked HASH hydrogel.
[0146] Then, 10 mg / mL cross-linked HASH hydrogel and 20 mg / mL cross-linked HASH hydrogel were dispersed in equal volume ratios into a 10 mg / mL rhCol Ⅲ solution (during the dispersion process, the cross-linked HASH gel formed small particles distributed in the recombinant collagen solution) to obtain a physically mixed hydrogel, wherein the rhCol Ⅲ content was 3 mg / mL and the HASH content was 5 mg / mL and 10 mg / mL, respectively.
[0147] To simulate the diffusion and release effect of rhCol III molecules under the influence of body fluids after the above-mentioned hydrogel is applied to the lesion site, the prepared rhCol III-HASH composite hydrogel and the physically mixed hydrogel were immersed in physiological saline. The saline solution was aspirated at 1 hour and 24 hours, and the protein concentration was measured (using a BCA protein assay kit). The results are shown below. Figure 7The physically mixed hydrogels prepared above are merely simple physical mixtures of substances; specifically, they are heterogeneous two-phase gels composed of cross-linked HASH gel particles (simple HASH hydrogels) dispersed in rhCol III solution. Figure 7 It is evident that the release rate of rhCol III in physically composite hydrogels is very rapid, completely diffusing and releasing into physiological saline within 1 hour. However, the rhColIII-HASH composite hydrogel of this invention, due to its semi-interpenetrating polymer network structure, is a single-phase homogeneous gel uniformly dispersed at the molecular level. rhCol III molecules are uniformly distributed and embedded in the cross-linked network of HASH in their original molecular form, thus achieving a much slower diffusion and release. Figure 7 It is evident that the release rate of rhCol III is relatively slow, with less than 80% of rhCol III being released within 24 hours.
[0148] Example 11
[0149] This case study investigated the cell adhesion properties of rhCol I-HASH composite hydrogels and rhCol III-HASH composite hydrogels.
[0150] Following the preparation method in Example 8, rhCol I-HASH composite hydrogels and rhCol III-HASH composite hydrogels were prepared in 12-well cell culture plates. The HASH content in both composite hydrogels was 10 mg / mL, and the rhCol I and rhCol III contents were both 3 mg / mL. The amount of each composite hydrogel in the 12-well cell culture plate was 1 mL / well. 2 mL of cell culture medium (DMEM, 12% fetal bovine serum) and 1×10⁻⁶ HASH hydrogels were added to each well. 5 NIH / 3T3 fibroblasts were cultured for 24 to 96 hours, with a blank cell culture plate as a control. The cells were fixed with 0.4 mL of 10% formalin solution, stained with crystal violet, and observed under a microscope. The results are as follows: Figure 8 As shown. By Figure 8 As can be seen, NIH / 3T3 fibroblasts adhered and spread well on the control blank culture plate. Although recombinant human collagen (rhCol I, rhCol III) alone has cell adhesion sites, in rhCol I-HASH composite hydrogels and rhCol III-HASH composite hydrogels, because the recombinant human collagen does not participate in cross-linking and is not fixed in the cross-linking network, it cannot serve as an anchor point for cell adhesion and fixation, and therefore does not have cell adhesion function. This characteristic is advantageous for postoperative adhesion repair treatment.
[0151] Example 12
[0152] This case study examines the application effects of rhCol III solution, cross-linked HASH hydrogel, and rhCol III-HASH composite hydrogel in the treatment of intrauterine adhesions.
[0153] An animal model of intrauterine adhesions was established by selecting 8-week-old female SPF-grade SD rats (200g-220g) in estrus.
[0154] The estrus period was determined using the vaginal smear method: at a fixed time each day, 150µL of physiological saline was drawn with a 200µL pipette tip, gently inserted into the rat's vagina about 0.5cm, blown and then drawn again, and evenly smeared onto a glass slide. After air drying, it was fixed with anhydrous ethanol, air-dried, stained with crystal violet for 2-3 minutes, washed with water, and air-dried. Cell morphology was observed under an optical microscope (estrus period characteristics: keratinized epithelial cells account for >90%, no leukocytes or epithelial cell debris), and rats in estrus were selected.
[0155] After fasting for 12 hours with free access to water, rats were anesthetized and fixed supine on the operating table. The abdomen was shaved and disinfected. An incision of approximately 2-3 cm was made along the midline of the abdomen, exposing the uterus. The surrounding adipose tissue was gently separated with forceps. Using ophthalmic scissors, a 0.3 cm notch was made on the left side of the uterus, 0.5 cm above the cervix. A sterile curettage spoon was inserted and gently scraped along the long axis of the uterus to ensure uniform endometrial damage. Subsequently, 10 µL of lipopolysaccharide (LPS) and 100 µL of experimental sample were injected sequentially into the uterine cavity through the incision. The uterus was then repositioned, and the uterus, abdominal muscles, and skin were sutured layer by layer with surgical sutures. The incision was cleaned and disinfected, and penicillin (200 mg / kg) was administered intramuscularly. Postoperatively, the rats were housed individually with free access to food and water. Their mental state, food intake, and incision healing were observed daily.
[0156] Postoperatively, the estrous cycle of rats was monitored daily using vaginal smears. The time when each rat entered the second estrous phase was recorded, and the experiment was terminated on the same day as the second estrous phase. Rats were euthanized using an overdose anesthesia method, and the uterus was exposed by re-exploration of the abdomen. The appearance of the uterus was observed with the naked eye (e.g., whether there were adhesions or congestion). The uterus was cut open with ophthalmic scissors, and the intact uterine tissue was removed. The surface bloodstains were rinsed with sterile physiological saline. The left uterus was fixed in 4% paraformaldehyde fixative, dehydrated in a gradient of ethanol, then embedded in paraffin, sectioned, and stained with hematoxylin and eosin (HE).
[0157] Tissue sections were observed under an optical microscope, and the degree of intrauterine adhesions was assessed according to the AFS 1988 scoring system: adhesion range 0-4 points, adhesion type 0-4 points, menstrual abnormality 0-2 points (in rats, the estrus cycle and uterine abnormalities were considered together for comprehensive judgment), and total score 0-10 points, with higher scores indicating more severe adhesions. Simultaneously, quantitative observation and analysis were performed on: endometrial thickness (measured at 5 random points, averaged) and glandular number (counted in 5 random fields of view under high magnification, averaged).
[0158] A total of 25 animals were included and divided into 5 groups, as shown in Table 4 below. The test samples for groups 4 and 5 were the rhCol III-HASH composite hydrogel (rhCol III 5 mg / mL, HASH 5 mg / mL, HASH thiolization modification degree 1.18%) and cross-linked HASH hydrogel (HASH 5 mg / mL, thiolization modification degree 1.18%) prepared in Example 6, respectively. Group 1 was the sham surgery group; after laparotomy, only 100 µL of physiological saline was injected into the cavity through the uterine incision, without curettage, and 10 µL of lipopolysaccharide (LPS) was not injected.
[0159] Table 4 Test Samples of Each Group
[0160]
[0161] The test results are shown in Figure 9 .Depend on Figure 9 As can be seen, compared with physiological saline (model group) (group 2), rhCol III solution (group 3), and cross-linked HASH hydrogel (group 5), rhCol III-HASH composite hydrogel (group 4) has the most ideal therapeutic effect, reflected in the lowest adhesion AFS total score, the highest number of glands, and the highest endometrial thickness. The therapeutic effect of rhCol III solution alone (group 3) is not significant; the AFS total score, number of glands, and endometrial thickness are all close to those of physiological saline (model group) (group 2). Cross-linked HASH hydrogel (group 5) is superior to physiological saline (model group) (group 2) and rhCol III solution (group 3), but inferior to rhCol III-HASH composite hydrogel (group 4).
[0162] Example 13
[0163] This case study examines the efficacy of rhCol III solution, cross-linked HASH hydrogel, and rhCol III-HASH composite hydrogel in the treatment of menopausal urogenital syndrome (GSM).
[0164] Genitourinary syndrome of menopause (GSM) refers to a collection of symptoms and signs in women during the menopausal transition and postmenopausal period, caused by decreased levels of estrogen and other sex hormones, including atrophy of the reproductive and urinary tracts and sexual dysfunction. GSM reproductive system symptoms include vulvar and vaginal dryness, burning, irritation, and sexual dysfunction due to insufficient vaginal lubrication. Urinary system symptoms include urinary urgency, dysuria, and recurrent lower urinary tract infections, severely impacting women's health and quality of life.
[0165] Female SPF-grade SD rats (250-300g) were selected. A GSM animal model was established according to the method reported by Yang et al. (Comparative Medicine of Experimental Animals, 2022, 42(6):531-539). A longitudinal incision was made 0.5-1.0 cm on both sides of the midline of the rat's back. The abdomen was entered layer by layer, and the bilateral ovaries of the rats were removed. The muscles and skin were sutured layer by layer. The incision was cleaned and disinfected. Penicillin (200mg / kg) was injected intramuscularly. After the operation, the rats were allowed free access to food and water. The rats were observed daily for their appearance, general behavior, mental state, wound healing, respiratory status, fecal characteristics and color, genitals, death, and other abnormalities.
[0166] Starting from the 7th day after surgery, vaginal exfoliated cell smears were examined for 5 consecutive days. If the rats did not show cyclical changes and the uterus showed significant atrophy at the end of the experiment, the model was considered successfully established and included in the experimental results.
[0167] On postoperative day 14, 0.5 mL of test sample was injected into the vagina of the rats every two days for seven consecutive days. The rats were anesthetized and euthanized, and their body weight was measured. Then, the vagina was dissected, removed, and its wet weight was measured. The "vaginal index" was calculated as: vaginal wet weight / rat body weight × 100%. The sample was then fixed in 4% paraformaldehyde fixative, dehydrated in a gradient of ethanol, embedded in paraffin, sectioned, and stained with hematoxylin and eosin (HE).
[0168] A total of 36 animals were included and divided into 6 groups, as shown in Table 5. The test samples of groups 3 to 6 were prepared according to the method in Example 8, with a HASH thiolization modification degree of 1.18%, a HASH content of 8 mg / mL, and rhCol III contents of 0 mg / mL, 2 mg / mL, 4 mg / mL, and 8 mg / mL, respectively.
[0169] Table 5. Test samples for each group
[0170]
[0171] See the test results. Figure 10 .Depend on Figure 10As can be seen, compared with physiological saline (group 1) and rhCol III solution (group 2), rhCol III-HASH composite hydrogel (groups 4 to 6) showed better therapeutic effects, as evidenced by a higher vaginal index, indicating that it can effectively prevent or alleviate vaginal atrophy caused by ovariectomy in rats. The therapeutic effect of rhCol III solution (group 2) was not significant, and the vaginal index was similar to that of physiological saline (group 2). Cross-linked HASH hydrogel (group 3) was superior to physiological saline (group 1) and rhCol III solution (group 2), but weaker than rhCol III-HASH composite hydrogel (groups 4 to 6).
[0172] The results of histological evaluation were consistent with those of vaginal index evaluation. Compared with rhCol III-HASH composite hydrogel (groups 4 to 6), the mucosa and muscle layers of the rat vaginal wall were significantly thinner in physiological saline (group 1) and rhCol III solution (group 2), indicating that physiological saline and rhCol III solution could not effectively prevent or alleviate vaginal atrophy caused by ovariectomy in rats.
[0173] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel, characterized in that, The composite hydrogel has a semi-interpenetrating polymer network structure. The thiolized hyaluronic acid is prepared by thiolization modification of the carboxyl groups of the hyaluronic acid side chain. The thiolized hyaluronic acid forms a cross-linked network through the self-cross-linking reaction between thiol groups. The recombinant humanized collagen does not undergo cross-linking and is uniformly distributed and embedded in the cross-linked network. The degree of modification of the thiolized hyaluronic acid is 0.5%~2%; The content of the thiolized hyaluronic acid in the composite hydrogel is 4 mg / mL to 10 mg / mL. The content of the recombinant humanized collagen in the composite hydrogel is 3 mg / mL to 10 mg / mL; The recombinant humanized collagen is selected from one or more of recombinant type I humanized collagen, recombinant type III humanized collagen, recombinant type V humanized collagen, and recombinant type XVII humanized collagen; The preparation method of the recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel includes the following steps: S1. Dissolve recombinant humanized collagen in an aqueous solvent to form a first solution, adjust or not adjust the pH of the first solution to a physiologically acceptable neutral range, and perform or not perform aseptic filtration; S2. Dissolve thiolized hyaluronic acid in an aqueous solvent to form a second solution, adjust or not adjust the pH of the second solution to a physiologically acceptable neutral range, and perform or not perform aseptic filtration; S3. Mix the first solution and the second solution evenly according to the formula, and perform sterile filtration or not. After mixing, the thiol groups of the thiolized hyaluronic acid in the second solution form a self-crosslinking network of disulfide bonds under the action of oxygen. After the crosslinking is stable, a colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel is obtained. The aqueous solvents mentioned in S1 and S2 are both selected from physiological saline or phosphate buffer; the physiologically acceptable neutral range is pH = 6.8~7.
6.
2. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 1, characterized in that, The degree of modification of the thiolized hyaluronic acid is 0.7%~1.2%.
3. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 2, characterized in that, The content of the thiolized hyaluronic acid in the composite hydrogel is 5 mg / mL to 8 mg / mL.
4. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 1, characterized in that, The weight-average molecular weight of the hyaluronic acid or its salt is 0.05 MDa to 3.0 MDa.
5. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 4, characterized in that, The weight-average molecular weight of the hyaluronic acid or its salt is 0.1 MDa to 1.0 MDa.
6. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 5, characterized in that, The weight-average molecular weight of the hyaluronic acid or its salt is 0.15 MDa to 0.5 MDa.
7. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 1, characterized in that, The recombinant humanized collagen has a weight-average molecular weight greater than 10 kDa.
8. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 7, characterized in that, The recombinant humanized collagen is selected from recombinant type I humanized collagen and / or recombinant type III humanized collagen; the weight-average molecular weight of the recombinant humanized collagen is greater than 20 kDa.
9. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 8, characterized in that, The recombinant humanized collagen is selected from recombinant type III humanized collagen.
10. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to any one of claims 1-9, characterized in that, The dynamic viscosity of the composite hydrogel is greater than 5 × 10⁻⁶. 4 mPa·s.
11. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 10, characterized in that, The dynamic viscosity of the composite hydrogel is greater than 10 × 10⁻⁶. 4 mPa·s.
12. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to any one of claims 1-9, characterized in that, The composite hydrogel is in a sterile state, which is achieved through moist heat sterilization.
13. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 1, characterized in that, When the pH value is not adjusted in S1 and / or S2, the pH value is adjusted to a physiologically acceptable neutral range after the first solution and the second solution are mixed evenly in S3.
14. The colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to claim 13, characterized in that, The preparation method further includes a moist heat sterilization process, wherein the moist heat sterilization process is performed immediately after the first solution and the second solution are mixed evenly, or after the cross-linking is stabilized to obtain a colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel; the temperature of the moist heat sterilization process is in the range of 120℃~123℃ and the sterilization time is at least 15 minutes.
15. The use of the colorless and transparent recombinant humanized collagen-thiolized hyaluronic acid composite hydrogel according to any one of claims 1-14 in the preparation of postoperative adhesion repair treatment agents, in the preparation of skin wound repair treatment agents, or in the preparation of postmenopausal urogenital syndrome treatment agents.
Citation Information
Patent Citations
Low-sulfhydrylation-modification-degree biocompatible high-molecular sulfhydrylation derivatives, cross-linking material thereof, and purpose thereof
CN102399295A
Preparation method and application of sulfhydryl / disulfide bond controllable self-crosslinked hyaluronic acid hydrogel
CN104892962A
Controllable self-crosslinking sulfhydrylated hyaluronic acid-collagen composite hydrogel as well as preparation method and application thereof
CN108084461A
Mandibular condylar osteochondral repair scaffold material and preparation method thereof
CN112618800A
Preparation method and application of compound temperature-sensitive recombinant collagen hydrogel
CN115804750A